The Effect of Inflation on Poverty Levels In West Sulawesi Province, Indonesia - Masita, M.; Halim , Abdul; Frida Suryati, Tri (Golden Ratio of Social Science and Education, 2024)
Arsyad, L. (2016). Development Economics. Fifth Edition. Yogyakarta: UPP STIM YKPN.Ayunita, K. (2018). The Effect of Inflation and Education on Unemployment and Poverty in Bali Province. E-Journal EP Unud. Faculty of Economics and Business, Udayana University Bali. Vol. 9 No. 6, pp. 1373-140.Central Bureau of Statistics (BPS) of West Sulawesi. (2014-2023). West Sulawesi in Figures. Mamuju: BPS West Sulawesi. Accessed from www.bpsmamujukab.go.id.Chamsyah, B. (2008). Reinventing Social Development for the Welfare of Indonesian Society. Jakarta: Trisakti University Press.Conway, G. (2019). The Doubly Green Revolution: Food for All in the 21st Century. Ithaca: Cornell University Press.Hardinandar, N. (2019). Sociology of Development. Jakarta: Kencana Prenada Media Group.Jhingan, M. L. (2014). Economics of Development and Planning. 40th Edition. New Delhi: Vrinda Publications.Jhingan, M. L. (2014). Development Economics and Planning. Jakarta: PT Raja Grafindo Persada.Kristin, A. (2018). The Effect of Inflation and Education on Unemployment and Poverty in Bali Province. Journal of Economics and Development, 9(2): 144-158.Regional Office of the Directorate General of Treasury of West Sulawesi Province (2024). Regional Fiscal Study Year 2023. Mamuju. Regional Office of the Directorate General of Treasury of West Sulawesi Province. Accessed from : 2023_Q4_KFR_Province_Sulawesi_Barat.pdf - Google Drive. Mardiatiillah, R. (2021). The Effect of Unemployment and Inflation on Poverty Level in South Sumatra in 2015-2019. Journal of Economics and Development, 10(3): 280-290.Muhammad. (2022). Poverty in Indonesia: A Review. Yogyakarta: Deepublish.Muhammad, A., Okuputra, & Nasikh. (2022). The Effect of Regional Innovation on Poverty. Journal of Finance Economics and Management (Innovation), Vol. 8 No. 1.Muh. Taufik, Abdul Halim, & Tri Frida Suryati. (2023). The Effect of Inflation on the Unemployment Rate in Mamuju Regency. Journal of Economics, Management and Accounting (Forum Ekonomi), Volume 25, Issue 4, pp. 679-706.Oktaviana. (2021). Analysis of the Effect of Economic Growth, District Minimum Wage, and Unemployment on Poverty in Madiun Regency. Syntax Idea Journal, 4(1), 6.Putong, I. (2018). Introduction to Macroeconomics. Jakarta: Ghalia Indonesia.Rezki, A. (2022). The Effect of Inflation Economic Growth and Unemployment on Poverty Level in Surabaya City. Journal of Economics, Faculty of Economics and Business, Surabaya State University. Vol. 2 No. 1, pp. 175-186, ISSN: 2798-5008.Rezki Mardiatiillah. (2021). The Effect of Unemployment and Inflation on the Poverty Rate in South Sumatra in 2015-2019. ISSN: 1907-3011-EiSSN: 2528-1127.Silalahi, U. (2012). Social Research Methods. Bandung: PT Refika Aditama.Sujarweni, V. W. (2015). SPSS for Research. Yogyakarta: New Library Press.Sugiar Tningsih, K.S. (2017). The Effect of Inflation on Poverty in Indonesia for the Period 1998-2004. ISSN 2256-3936. July 20, Bandung.Sugiyono. (2012). Quantitative, Qualitative and R&D Research Methods. Bandung: Alfabeta.Suparto. (2014). Statistics for Research. Jakarta: PT RajaGrafindo Persada.Todaro, M. P., & Smith, S. C. (2015). Economic Development. 12th Edition. Harlow: Pearson Education Limited.